OP15 The role of material, psychological and behavioural factors in mediating the association between socio-economic position and allostatic load: Evidence from the 1950s cohort of the West of Scotland Twenty-07 Study. (2nd September 2014) - Robertson, T; Benzeval, M; Whitley, E; Popham, F
Abstract : Background: Lower socio-economic position (SEP) accumulated across the lifecourse has been found to be associated with higher allostatic load, a summative score that utilises a number of biomarker measures across multiple physiological systems. Using allostatic load, rather than individual biomarkers, allows us to investigate the synergistic nature of the cumulative physiological burden on the body imposed by exposure to damaging environmental stressors. This study examines potential mediators of the association between SEP and allostatic load, including material, psychological and behavioural factors, measured over the lifecourse. Methods: Data are from the West of Scotland Twenty-07 Study, with respondents followed over five waves from ages 35 to 55 (n = 999). Allostatic load was measured by summing nine binary biomarker scores ('1' = in the highest-risk quartile) measured at age 55. SEP was measured as a person's most common working age social class across the 20 years of follow-up. All mediators were measured at baseline and 20 years later. Material mediators included car and home ownership, and having low income. The General Health Questionnaire (GHQ-12) was used as the psychological mediator. Behavioural mediators included smoking, alcohol consumption, physical activity and diet. Sex-adjusted linear regression models were used to assess the degree of attenuation of the SEP-allostatic load associations due to adjustment for the mediators. Results: Higher SEP was found to be associated with lower allostatic load (difference in allostatic load in manual versus non-manual SEP respondents (β)=-0.60, 95% CI=-0.96, -0.24). Simultaneous adjustment for all potential mediators (at both measurement points and accumulated over time) fully attenuated the association between SEP and allostatic load. Analyses by mediator type revealed that renting one's home (100% attenuation; β=0.05; 95% CI=-0.34, 0.43) and having low income (78% attenuation; β=-0.13; 95% CI=-0.45, 0.19) across both waves largely attenuated the SEP-allostatic load association. Cumulative smoking across both waves had the strongest behavioural attenuation effect (by 43%; β=-0.34, 95% CI=-0.73, 0.06). None of the other health behaviours attenuated the association substantially. GHQ did not attenuate the association. Conclusion: Material factors and smoking have important roles in explaining socio-economic disparities in allostatic load, particularly when accumulated over time. These findings are important in understanding the pathways between SEP and health to better inform policies and programmes to reduce these inequalities.